Epidemiological Situation on Leptospirosis in the Rostov Region in 2024 - E. A. Bereznyak; A. V. Trishina; N. V. Breneva; Yu. A. Lyubich; N. L. Pichurina; I. V. Morozova; D. I. Simakova; O. P. Dobrovol’sky; A. V. Zabashta; A. Yu. Goncharov; E. V. Kovalev; N. E. Gaevskaya (Проблемы особо опасных инфекций)
The aim of the study was to investigate the leptospirosis manifestation peculiarities in the Rostov Region with an assessment of the natural foci epizootic activity and the epidemic significance of infection. Materials and methods. In 2024, an epizootiological study of 15 administrative territories was conducted. Small mammals (314 specimens of 12 species) were captured in open stations. The material from the animals was studied using bacteriological, microscopic, serological and molecular-genetic methods. The testing of 577 blood sera of people from selected groups of conventionally healthy population living in the 18 administrative districts of Rostov Region and Rostov-on-Don city was conducted using ELISA with detection of IgG and IgM to leptospirosis causative agents. Results and discussion. Specific antibodies to leptospirosis pathogens in animals were found in 11.5 % of samples from nine species of small mammals: house mouse, pygmy wood mouse, field vole, yellow-necked mouse, mound-building mouse, lesser white-toothed shrew, pygmy shrew, social vole, brown rat. Leptospira spp. infecting serogroups have been identified: Sejroe, Icterohaemorrhagiae, Canicola, Grippotyphosa, Pomona, Tarassovi. PCR-positive result was obtained for a sample from a pygmy wood mouse. Seroepidemiological studies of the conventionally healthy population have revealed the presence of specific antibodies to Leptospira in their blood in 14 administrative territories. The total level of seroprevalence was 12.7 %. The serogroup structure of the immune layer of the population in the Rostov Region is as follows: Grippotyphosa (28.5 %), Pomona (23.2 %), Canicola (21.4 %), Tarassovi (7.1 %), Sejroe (5.3 %). Positive reactions to several serogroups were noted in a number of serа. The conducted studies evidence the existance of active natural foci of leptospirosis on the territory of the Rostov Region and involvement of the population in the epidemic process.